PERTUMBUHAN DAN PRODUKSI BAHAN KERING ECENG GONDOK SEBAGAI SUMBER DAYA PAKAN DI PERAIRAN YANG MENDAPATKAN LIMBAH KOTORAN ITIK - Zahmi, Hesti Reva Helva Ari; Sumarsono, Sumarsono; Anwar, Syaiful (Animal Agriculture Journal, 2012)
A study was conducted to assess the provision of duck manure on growth and dry matter production of water hyacinth as a feed resource. This research used Completely Randomized Design (CRD) with 5 treatments and 4 replications, providing sewage ducks in each treatment (T0; 0 g / l of water, T1, 5 g / l of water, T2, 10 g / l of water , T3; 15 g / l of water, and T4; 20 g / l of water). Parameters measured were growth and dry matter production. Data were analyzed using analysis of variance (significance level of 5%) followed by Duncan Multiple Range Test to see different test and trials Orthogonal Polynomials. The results showed that the addition of duck manure in water hyacinth plants can enhance the growth of Total Leaf weeks 6 and dry matter production. Growth in the number of leaf-6 weeks to the highest achieved in the addition of duck manure 12,91 g / l with real predictive value of 233 strands, but not on plant height and leaf area, while the highest dry matter production achieved in the addition of duck manure as much as 12 g / l with real predictive value of 18,56 g.Keywords: duck manure, water hyacinth, growth, dry matter production